2014
DOI: 10.3329/bjp.v9i4.20481
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and apoptosis-inducing effects of <i>Moringa concanensis</i> using hepG2 cell lines

Abstract: The objective of the present investigation is focused on the anti-cancer activity of the ethanolic crude extract of Moringa concanensis leaf and bark against HepG2 cell line. The study was facilitated by collecting the plant sample and subjected to ethanol crude extraction. The anti-cancer activity of the crude extracted sample against HepG2 cell line was examined by MTT assay. The study confirms that the leaf crude extract of M. concanensis has pronounced anti-cancer potential against HepG2 cell lines while c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Crude plant extracts are screened on cell culture, to determine their efficiency as a potential alternate drug and also to check their efficiency in clinical application as suggested by Balamurugan et al (2014). Plants are primary resources for antioxidants like carotenes, phenolic acids, etc., the phytochemical analysis Tecoma stans revealed that the plant has alkaloids, steroids, glycosides and carbohydrates as suggested by (Prajapati, Patel, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crude plant extracts are screened on cell culture, to determine their efficiency as a potential alternate drug and also to check their efficiency in clinical application as suggested by Balamurugan et al (2014). Plants are primary resources for antioxidants like carotenes, phenolic acids, etc., the phytochemical analysis Tecoma stans revealed that the plant has alkaloids, steroids, glycosides and carbohydrates as suggested by (Prajapati, Patel, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…An extensively used treatment for cancer is chemotherapy and one of the major drawbacks is the toxicity that is caused to the normal cells due to the inability of the chemical drugs to differentiate between normal and cancerous cells (Balamurugan et al, 2014). Traditional medicines have been tested and researched upon to obtain an effective drug against cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports show that plant crude extracts replicate at tumor sites under hypoxic conditions and stimulate the host immune response and gene expression and leads to the inhibition of tumor growth [21]. In this research, C. gynandra a common medicinal plant used in the treatment of tumor was selected and evaluated for its cytotoxic potential employing in vitro methods.…”
Section: Resultsmentioning
confidence: 99%
“…Nimmo is one of the Indian medicinal plants belongs to the family of Moringaceae, used to treat various human diseases [5][6][7][8], M. concanensis Nimmo plant have confirmed anti-inflammatory [7,9], anticancer [10], analgesic [9], anti-pyretic [7], anti-implantation [11], anti-convulsant [12], anti-microbial anti-fungal [13] and antihyperglycemic activity [14]. To the best of our knowledge, Moringa concanensis Nimmo leaves extract have not been investigated for phytochemical profiles, free radical scavenging, and in vivo simulated in vitro antioxidant properties.…”
Section: Concanensismentioning
confidence: 99%